2020
DOI: 10.5021/ad.2020.32.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Adult Patients with Tinea Capitis in Southeastern Korea

Abstract: Background: Tinea capitis is a cutaneous infection of dermatophytes and predominant in children. Although tinea capitis in Korea is controlled by oral antifungal medications and concerted public health initiatives, it's still a health issue. Objective: To investigate changes in the epidemiological and mycological characteristics of adult patients with tinea capitis in southeastern Korea. Methods: Using medical records from Kyungpook National University Hospital and Catholic Skin Clinic from 1989 to 2018, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In Europe and Southeastern Korea, Microsporum canis is still the most commonly reported causative agent of tinea capitis. 4 , 10 In Portugal, the most common etiological agents are Microsporum audouinii (20%) and Trichophyton rubrum (20%). 9 Changing in hygiene conditions and lifestyle in America and England, have resulted in a different epidemiology of dermatophytosis, with Trichophyton tonsurans emerging as the most prevalent species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Europe and Southeastern Korea, Microsporum canis is still the most commonly reported causative agent of tinea capitis. 4 , 10 In Portugal, the most common etiological agents are Microsporum audouinii (20%) and Trichophyton rubrum (20%). 9 Changing in hygiene conditions and lifestyle in America and England, have resulted in a different epidemiology of dermatophytosis, with Trichophyton tonsurans emerging as the most prevalent species.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have shown an increasing incidence of tinea capitis in healthy adults, which emphasizes the necessity for greater attention to this condition in future research. 2 , 4 Adult tinea capitis often presents with mild inflammatory symptoms, making a challenge in differentiation from psoriasis capitis, seborrheic dermatitis and atopic dermatitis of the scalp. 5 This might be attributed to the development of sebaceous glands during puberty, which secrete long-chain fatty acids known for their antifungal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective, the strength of this study is provision of a detailed overview of the epidemiology of the fungal cultures of skin, analysis of dermatophyte detections worldwide. Many cover ss al one, 15,18,19,21,23,24,27,29,30,31,44,45,46,47,48,49,50 others cover onychomycosis and tinea pedis alone, 39,40,41,50,51,52,53,54,55,56,57,58,59,60,61,62,63 including the only article in this search from the UK and Ireland. 61 Eighteen articles were identified where all dermatomycoses were analysed, 14,16,17,20,22,26,28,64,65,66,67,68,69,70,71,72,73,74 but just five of…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other regions remain predominated by zoophilic species, prinicipally Microsporum canis (e.g. Greece, 24 Germany, 25 Romania, 26 Algeria, 27 Argentina, 28 Brazil, 29 Korea 30 and Taiwan 31 ). It is also postulated that infections from some nominally zoophilic strains may indeed be of human origin, as evidenced by a clonal strain of Trichophyton mentagrophytes detected in a cluster of pubogenital infections in Germany for which no animal source has been found till date 32 …”
Section: Introductionmentioning
confidence: 99%